PENGARUH FREKUENSI BERKUNJUNG SISWA KE PERPUSTAKAAN DAN FASILITAS PERPUSTAKAAN TERHADAP HASIL BELAJAR SISWA - ERNA MIFTAHUL J (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Library is the pivotal source of learning at school, due to the fact that both of the educators and students have the same chances to broaden their knowledge through library. Library as the important educational tool regards high beneficial to enhance educational quality in particular to improve the student grade. Henceforth, the lacking of student’s motivation at this Vocational High School to study regards as the cause of the student’s grade haven’t achieved their best. As a result, students must study hard and make a good use of the library to achieve good mark in learning. This research is done for revealing the influence of the frequent attendance of students in the library and library equipment towards the student’s grade. This research uses associate quantitative approaches which utilizes questionnaire as a key instrument, then the result analyzed with double linear regression technique(teknik regresi linear ganda). The population is within all of the class of XI accounting program State Vocational High school 1 Kraksaan 2011/2012 academic year. The total samples of this research were the total of all students at class of XI accounting program which are 81 students. This research classifies as population research because of the total population were less than 100. Based on the data analysis there is a significance effect of the frequent of student’s attendance in the library towards the student’s grade. Simultaneously, the frequent of student’s attendance in the library affected the grade which 52,5% and the rest 47,5% influenced with other factors. Based on this research, the writer highly recommended the principal to encourage the students to visit the school library frequently, thence the school board must pay more attention to the books collection provides, services, lighting, catalogs, and enjoyable atmosphere. As the results, students frequently visit the library and make good uses of the library to collect information, reading, or doing school assignment. Key words: Frequent Attendance, Library Equipments and Student Grade